Dynamic Modeling and Nyquist Stability Analysis of a Non-Interacting Two-Tank Series Thermal System - Yogi Yolanda; Yola Bertilsya Hendri; Salma Liska; Lisa Legawati; Suhendri Suhendri; Alltop Amri Ya Habib; Zulfansyah Zulfansyah (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Series tank systems are vital in chemical industries but susceptible to mass and thermal disturbances, making stability analysis essential. This study models the level and temperature dynamics of a non-interacting two-tank system equipped with a heater in Tank-01, analyzing its stability via Nyquist plots. The methodology involves laboratory step-response experiments validated against mathematical models derived using Laplace Transforms and Explicit Euler methods. Results demonstrate the model closely matches experimental data; Tank-01 exhibits first-order characteristics, while Tank-02 functions as a second-order system. The physical system successfully handled +52% and -35% step disturbances within liquid height limits of 3–24 cm and feed flow rates of 40.33–136.5 cm³/s. Furthermore, Nyquist analysis confirms the open-loop thermal process is inherently stable across all tested capacities. Maximum level and thermal process gains were 0.3787 and 0.0062, respectively. Ultimately, this study confirms the non-interacting two-tank system possesses stable, self-regulating characteristics against load disturbances within operational limits.